When they came for me : the hidden diary of an apartheid prisoner - Schlapobersky, John R. (Berghahn Books, 2021)
"In 1969, while a student in South Africa, John Schlapobersky was arrested for opposing apartheid and tortured, detained and eventually deported. Interrogated through sleep deprivation, he later wrote secretly in solitary confinement about the struggle for survival. In this exquisitely written memoir, the author reflects on the singing of the condemned prisoners, the poetry, songs and texts that saw him through his ordeal, and its impact. This sense of hope through which he transformed his life guides his continuing work as a psychotherapist and his focus on the rehabilitation of others. Apartheid and its resistance come to life in this story to make it a vital historical document, one of its time and one for our own"--